Using Idea Listing Technique in Teaching writing Recount Text to Junior High School Students - Yaumil Fadhila; Sitti Fatimah (Universitas Negeri Padang, 2020)
Abstract This paper aims to explain the reader how to teach junior high school by implementing idea listing technique. Idea Listing technique is an appropriate technique to teach writing. The product of writing is affected by the content as one as component of writing. Content is dominated by how brainstorming goes. In writing students often get problem in organizing their ideas or brainstorming their ideas that has big impact to produce a good writing. ILT can help students to overcome or solve the problem. It becomes the reason why this paper is written. In Idea Listing technique students are asked to produce the idea in short time and put it on the paper to keep their idea and then relate it with the topic. This technique is more effective and suitable to solve the problem and can improve students writing, attention, ability and motivation in writing process. Key words: Writing, Teaching Writing, ILT